Respon Santri Putri Terhadap Pelatihan Budidaya Tanaman Hidroponik dengan Wadah Styrofoam - Muis, Sahribulan; Hala, Yusminah; Hiola, St. Fatmah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
Hydroponics is a way of cultivating plants using water that has been dissolved in the nutrients needed by plants as a medium for plant growth to replace soil. The concentration of nutrient solution must be maintained at a certain level for optimal plant growth and production. The activity implementation method is divided into 2 main stages, namely: the preparation stage and the implementation stage. In this preparatory stage, the implementation team did several things, namely coordinating the team with the service team in preparing for the implementation of the activities. The implementation stage that will be carried out in hydroponic plant cultivation training is divided into 3 stages, namely presentation, demonstration and implementation practice. After attending the training, the students' interest in hydroponic farming has increased and the students have come up with the idea of ​​making hydroponics with Styrofoam containers in the school yard in front of the dormitory where they live. In addition, many students are interested in developing hydroponic plant cultivation in the future.